The acute and medium-term effects of treatment with electroconvulsive therapy on memory in patients with major depressive disorder. Issue 4 (23rd October 2015) - Maric, N. P.; Stojanovic, Z.; Andric, S.; Soldatovic, I.; Dolic, M.; Spiric, Z.
Abstract : Background: Current literature provides insufficient information on the degree of cognitive impairment during and after electroconvulsive therapy (ECT), mostly due to the fact that applied tests lacked sensitivity and flexibility. Our goal was to evaluate cognitive functioning in adult depressed patients treated with bi-temporal ECT, using tests sensitive for detection of possible acute and medium-term memory changes. Method: Thirty adult patients with major depressive disorder, treated with a course of bi-temporal ECT, underwent clinical and cognitive measurements three times: at baseline, immediately after a course of ECT, and 1 month later. For cognition assessment, we used learning and visual, spatial and figural memory tests from the Cambridge Neuropsychological Test Automated Battery (CANTAB). Results: Bi-temporal ECT has proven to be an effective treatment. The linear mixed model, used to analyze changes in depression severity and patients' cognitive performances over time and to assess dynamic correlations between aforementioned features, did not show any significant memory impairment as a potential acute or medium-term ECT effect. However, it yielded significant improvement on visual memory and learning at the follow-up, which positively correlated with the improvement of depression. Conclusion: Good progress is being made in the search for ECT-related acute and medium-term cognitive side-effects by using the tests sensitive to detect memory dysfunction with parallel forms of the tasks (to counter practice effects on repeat testing). Our results on learning and memory in relation to ECT during treatment of depression did not bring forth any prolonged and significant bi-temporal ECT-related memory deficit.